Measuring wanting and liking from animals to humans: A systematic review. (April 2016) - Pool, Eva; Sennwald, Vanessa; Delplanque, Sylvain; Brosch, Tobias; Sander, David
Highlights: Animal research showed that is possible to want a reward that is not liked, human research produced contradictory results. This discrepancy could be due to inconstancies in concept operationalizations. We systematically reviewed methodologies used to assed wanting and liking in humans. Expected pleasantness represents a source of confound for wanting and liking operationalizations in humans Abstract: Animal research has shown it is possible to want a reward that is not liked once obtained. Although these findings have elicited interest, human experiments have produced contradictory results, raising doubts about the existence of separate wanting and liking influences in human reward processing. This discrepancy could be due to inconsistences in the operationalization of these concepts. We systematically reviewed the methodologies used to assess human wanting and/or liking and found that most studies operationalized these concepts in congruency with the animal literature. Nonetheless, numerous studies operationalized wanting in similar ways to those that operationalized liking. These contradictions might be driven by a major source of confound: expected pleasantness. Expected pleasantness underlies cognitive desires and does not correspond to animal liking, a hedonic experience, or to animal wanting, which relies on affective relevance, consisting of the perception of a cue associated with a relevant reward for the organism's current physiological state. Extending the concept of affective relevance and differentiating it from expected pleasantness might improve measures of human wanting and liking.